Membumikan Khilafah di Indonesia: Strategi Mobilisasi Opini Publik oleh Hizbut Tahrir Indonesia (HTI) di Media Sosial - Paelani Setia (Journal of Society and Development, 2021)
Social media, with its openness, provides new cyberspace that religious organizations use in conveying their religious messages, including the religious message of the Hizbut Tahrir Indonesia (HTI) organization. This paper aims to discuss the strategy of Hizbut Tahrir Indonesia (HTI) in influencing public opinion on social media after it was dissolved by the government through Perppu Ormas Number 2 of 2017. This study uses a qualitative method with data collection through online observations, field observations, interviews, and document reviews. This paper finds that HTI's struggle to ground the Khilafah ideology on social media is quite successful because it can take advantage of the momentum of national political dynamics. While social media is used as an essential instrument for disseminating Khilafah's opinion, various cases of post-truth political practice were also found. Unfortunately, the assumption that social media is safe for HTI, but that assumption has not been proven true. The criminal penalties received by its members have become a new threat to HTI on social media.